Feasibility, safety and efficacy of endoscopic single-operator cholangioscopy: a retrospective single-center study - Karsten Büringer; Ulrike Schempf; Stefano Fusco; Dörte Wichmann; Dietmar Stüker; Martin Götz; Nisar P. Malek; Christoph R. Werner (Therapeutic Advances in Gastroenterology)
Background: Endoscopic retrograde cholangiopancreaticography (ERCP) is the standard endoscopic procedure for the diagnosis and treatment of diseases of the pancreas and bile ducts. Cholangioscopy provides direct visualization of the bile ducts. It offers the possibility of more detailed diagnostic and therapeutic indications. Today, cholangioscopy is often performed as a single-operator (SOC) procedure. Objectives: We were interested in the clinical efficacy of our SOC procedure in comparison with published studies, and performed this retrospective data analysis of all our consecutive patients from 2016 to 2022 to analyze the feasibility, safety, and efficacy of SOC. Design and Methods: A retrospective single-center analysis of patients undergoing SOC at a tertiary center from 2016 to 2022 ( N  = 196) was performed. Demographic data, indication for SOC, exam-specific data, efficacy, and complications were included. Sensitivity and specificity for diagnosing indeterminate biliary strictures were calculated. Results: The most common indications for SOC were indeterminate biliary strictures ( n  = 117; 60%), treatment of biliary stones ( n  = 45; 23%), and other indications ( n  = 34; 17%), for example, foreign body removal or intraoperative SOC. In 97% of the SOC ( n  = 191), the procedure was technically successful. The diagnostic or therapeutic goal was achieved in 91% of SOC ( n  = 173). In the subgroup where the SOC result was confirmed by subsequent surgery ( n  = 93), sensitivity was 86%, specificity 99%, and SOC treatment of stones was successful in 89%. Complications occurred in (20%; n  = 37). The majority of these patients ( n  = 18; 10%) had minor bleeding requiring no intervention. Conclusion: SOC is an effective and safe procedure that should be the standard of care when primary diagnostic and/or therapeutic ERCP has failed. The sensitivity and specificity for determining the dignity of biliary strictures and the efficacy for the treatment of difficult-to-treat stones are reproducibly very high.